Relationship of maqasid al-shariah with al-qesas and diyah: analytical view - Muhammad Husni, Ahmad; Mohd Nor, Amir Husin; El-Seoudi, Abdel Wadoud Moustafa Moursi; Ibrahim, Ibnor Azli; Laluddin, Hayatullah; Samsudin, Muhammad Adib; Omar, Anwar Fakhri; Alias, Muhammad Nazir (Medwell Publications, 2012)
al-Qisas is considered in the Islamic law, the largest and the most important factors for the stability of justice in the society and the feeling of secure in the hearts of people, and it also preserving the human dignity and freedom. It is a purification for the murdered and the life of the mankind, and the healed for the oppressed and justice between the murderer and the murdered. It is an equality between punishment and crime. It is from the law of Allah Glory which His law that far above other that prescribed by the the corrupted minds suggestion and opinions of the misguided oppressive. The punishment in Islam tends to justice and the protection of virtue and morality. Thereby, it tends to be equal to the crime and its effects. Without al-Qisas, people attacked each other violently, al-Qisas is prevention to the evil consequences of the blood violation by crime. This wise legislation preserves the life of people and their organs. al-Qisas is aimed to achieve the equality between crime and punishment so that the penalty shall be equal to the crime committed as al-Qisas is similar deterrent punishment awaiting for the criminal who deters the victim and his guardian and the community who he lives in with this dreadful crime. In addition to these meanings, al-Qisas heals the rage of the victim and the rage of his heirs. Thus, i adopted in this study the inductive and analytical approach to gather the views of jurists, researchers, their evidences and arguments on the subject and texts related to it trying to perform fundamental and judicial analysis to suit the contemporary reality and the intent of the Sharia, and to the practical approach which study of the subject in the field and applied study. The Islamic Sharia developed wise legislation to keep the souls of the people and limbs from being assaulted. They made the punishment of killing intentionally in the highest degree of penalty it is death and made it to the guardian of the murdered the right of amnesty for free or a replacement of money, and set for the mistaken murder some penalties which makes him sensitive human in his actions and wise deeds and more alert, and rises above all indulgence and lack of caution. In which does not lead the neglecters to destroy the life or organs, and this wise legislation preserves the life of people and their organs.